PENYULUHAN AKTIVITAS SELF CARE SECARA DARING PADA PENDERITA DM TIPE II - Siti Mutia Kosassy; Rima Berlian Putri; Adelse Prima Mulya (Jurnal Abdimas Saintika, 2020)
Diabetes Mellittus (DM) is a chronic disease that cannot be cured, only everyone can control and be aware of. DM also causes complications. The main chronic complications are cardiovascular disease and stroke, diabetic foot, retinopathy, and diabetic nephropathy. DM clients have an increased risk of coronary artery disease 2-4 times higher than clients without DM. This complication is the main cause of death due to diabetes, which is 65%. The risk of stroke increases 2-4 times higher in DM clients. Peripheral vascular disease can lead to ulcers and leg amputations. This service activity aims to increase public knowledge of DM and be able to find out self-care activities for DM sufferers in the Mandiangin Bukittinggi Community Health Center. The method used for counseling / lectures and online discussions is the Zoom application. This activity went well and the participants were very active in asking questions. This activity is very effective in increasing public knowledge of DM and prevention of diabetes complications through self-care activities.Keywords: Diabetes Mellitus, People, Self care activity